Deconstructing the Local: The Aesthetic Space and Geographic Place of Oskar Morawetz's String Quartet no. 5 "A Tribute to Wolfgang Amadeus Mozart" (1991) - Sallis, Friedemann (Canadian University Music Review / Revue de musique des universités canadiennes, 2003)
The oppositional notions of centre and periphery, mainstream and margin, and universal and local have long been important criteria for the scholarly study of Western music. Indeed they are often taken for granted. This paper will take a critical look at the relationship obtaining between art music the notion of a national music. The object of study is taken from among the works of the Canadian composer (of Czech origin) Oskar Morawetz. The point is not to deny that music can be legitimately associated with a given place but rather to examine how these complex, problematic relationships are created and how they evolve and/or dissolve over time.